Quantitative Structure Activity Relationship of Riluzole Series as Anticonvulsants - GUNAKKUNRU, A.; VERMA, S.M. (Asian Journal of Chemistry, 2010)
24 Riluzole series, a blocker of excitatory amino acid (glutamic acid) mediated transmission, 2-benzothiazol-amines and 3-substituted 2-imino benzothiazolines have been subjected to quantitative structure activity relationship studies by step wise multiple regression analysis using steric, electronic descriptors. Result of this study has given 12 QSAR models and among all models one has statistically significant result (r > 0.97, F = 133.4899, q2 = 0.97753). Descriptors used in this study are: polarizability, density, molar refractivity, molar volume, average mass, parachor. Predictive ability of proposed model was assessed on the basis of regression data and cross validation parameters. This validated model brings important structural insight to model better anticonvulsant containing benzothiazole nucleus and more potent than riluzole.